Distinctive and Distinguished Gay‐Friendliness in Park Slope, New York City - Sylvie Tissot (Social Inclusion, 2023)
In this article, I argue that a new norm has emerged in former gay and now gentrified neighborhoods. Straight upper‐middle‐class residents claim to be gay‐friendly—an attitude that has not erased hierarchies, but has both displaced and instituted boundaries. Based on fieldwork in Park Slope, a neighborhood of Brooklyn, New York City, this article highlights that gay‐friendly markers signal acceptance as much as they work to establish heterosexuals’ moral authority and social privileges. Sociability between neighbors and friends is characterized by exchanges and interactions that have an impact on heterosexuals, yet remain primarily checked and filtered by them. In the domestic sphere, which is still structured by heterosexual (and gender) norms, significant restrictions on homosexuality persist. By analyzing progressiveness in relation to class and race, this study brings to light persistent power relations. It thus aims to contribute to the discussion about the extent, limits, and lingering ambivalences of a growing acceptance of homosexuality, which constitutes a significant dimension of so‐called inclusive cities.